Application of RFID internet of things for school empowerment towards smart school - Yoyon Efendi; Syahrul Imardi; Rometdo Muzawi; Muhammad Syaifullah (Peneliti Teknologi Teknik Indonesia, 2021)
State Vocational High School (SMK) 1 Perhentian Raja is a school located in Hangtuah village which is known as a catfish-producing village in Kampar Riau Regency, which has a major in Computer Network Engineering (TKJ) and Fisheries Cultivation. After making direct observations to the location of the Community Partnership Program (PKM), we found various forms of partner problems in education services, including student absenteeism which is still manual. The teacher will call the students one by one and then marked by the teacher on the attendance sheet. This will use teaching time in the classroom and laboratory, as a result learning activities will be less effective. This problem is also faced by librarians, with low student visits to the library. Meanwhile, other problems are parking services and school security. the condition of the school is still new, the condition of the school is still open will have an impact on the weakness of school security. especially with parking conditions that are still scattered and not neatly arranged, it will provoke crime in schools. 95 percent of students and teachers using motorized vehicles to school will make it difficult for school guards to maintain the vehicle. The solutions offered to achieve this PKM goal are Smart School Socialization, Internet of Things (IoT) training, Radio Frequency Identification (RFID) technology workshops, RFID Technology Training for Student Attendance and School Libraries, Parking RFID Assembly Training, and School CCTV Installation Training. , RFID and CCTV Maintenance Workshop. The output targets to be achieved from this PKM can be felt by students, teachers and schools. RFID and CCTV technology will provide educational services and school security. This PKM activity will have an impact on improving the quality of education and become one of the reference schools in the Perhentian Raja sub-district, Kampar district.